2003
DOI: 10.2135/cropsci2003.1340
|View full text |Cite
|
Sign up to set email alerts
|

Autumn Defoliation Effects on Alfalfa Winter Survival, Root Physiology, and Gene Expression

Abstract: before a killing freeze was imperative for winter survival and plant persistence. Cutting during cold hardening Harvesting alfalfa (Medicago sativa L.) after mid-September in lowered both plant persistence and root total nonstructhe North-Central USA often reduces plant winter survival, but the physiological mechanisms associated with poor winter survival are not tural carbohydrate (TNC) concentrations. However, understood. Our objective was to determine how autumn harvesting other research has shown that cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
(42 reference statements)
4
28
0
1
Order By: Relevance
“…Several other field observations, however, indicated that root TNC concentrations in fall and winter were not reduced by fall harvests, and were poorly related with yields in the following spring (Edminsten and Wolf 1988;Sheaffer et al 1988;Brink and Marten 1989). More recent research even showed an increase in TNC concentrations (g kg -1 DM) of taproots of alfalfa harvested in the fall Haagenson et al 2003). Dhont et al (2002Dhont et al ( , 2003, however, observed that the increase in total amounts (g plant -1 ) of TNC and N reserves in alfalfa taproots during fall was strongly limited by a fall harvest, especially with shorter regrowth intervals between the last two harvests (Fig.…”
Section: Organic Reservesmentioning
confidence: 95%
“…Several other field observations, however, indicated that root TNC concentrations in fall and winter were not reduced by fall harvests, and were poorly related with yields in the following spring (Edminsten and Wolf 1988;Sheaffer et al 1988;Brink and Marten 1989). More recent research even showed an increase in TNC concentrations (g kg -1 DM) of taproots of alfalfa harvested in the fall Haagenson et al 2003). Dhont et al (2002Dhont et al ( , 2003, however, observed that the increase in total amounts (g plant -1 ) of TNC and N reserves in alfalfa taproots during fall was strongly limited by a fall harvest, especially with shorter regrowth intervals between the last two harvests (Fig.…”
Section: Organic Reservesmentioning
confidence: 95%
“…Death of red clover occurred over winter because mowing reduced carbohydrate levels in the crown and roots; perennial legumes use 50 % of their stored carbohydrates to survive the winter (Sheaffer et al 1988). Producers in the Great Plains are encouraged to not harvest legumes in the fall to avoid stand loss due to winterkill (Haagenson et al 2004). …”
Section: Converting a Perennial Legume To Cropland Without Tillagementioning
confidence: 99%
“…Medicago falcata, which is a native legume species widely occurring in the cold areas of Russia, Mongolia, Scandinavia and northern China (Lesins and Lesins 1979), exhibits great tolerance to abiotic stresses such as drought and freezing, and is widely used as a general source of germplasm for breeding forage of alfalfa (Riday et al 2003). There are reports showing that freezing-tolerant alfalfa can accumulate COLDACCLIMA-TION-SPECIFIC (CAS) proteins during cold acclimation (Mohapatra et al 1989;Monroy et al 1993;Wolfraim et al 1993;Haagenson et al 2003). The CAS proteins belong to the family of dehydrin protein, and the expression of CAS genes in alfalfa genotypes is positively correlated with their tolerance to freezing (Mohapatra et al 1989).…”
mentioning
confidence: 99%